How does anisometropia affect the choroidal vascularity index? - Selim Cevher; Mehmet Barış Üçer; Tayfun Şahin (Indian Journal of Ophthalmology, 2022)
Purpose: To investigate the choroidal vascularity index (CVI) and morphological features of the choroid in anisometropic amblyopia. Methods: In this prospective cross-sectional study, 39 patients with unilateral anisometropic amblyopic patients and 33 eyes of 33 healthy control participants were involved. These participants were examined in terms of axial length (AL), spherical equivalent (SE), central macular thickness (CMT), choroidal thickness (CT), total choroidal area (TCA), luminal area (LA), stromal area (SA), LA/SA ratio, and CVI. All parameters were compared between amblyopic eyes, healthy fellow eyes, and healthy control eyes. The Shapiro–Wilk tests, Chi-square test, the paired t-test, Wilcoxon signed-rank test, Mann–Whitney U test, Kruskal–Wallis test, and Pearson/Spearman correlation tests were used. Results: In the hyperopic patients; SE, subfoveal CT, nasal CT, temporal CT, TCA, LA, SA, and CMT were greater in amblyopic eyes than in healthy fellow eyes and control eyes (P < 0.001, P < 0.001, P < 0.001, P < 0.001, P < 0.001, P < 0.001, and P < 0.001, respectively), and CVI, LA/SA ratio, and AL were smaller in amblyopic eyes than in healthy fellow eyes and control eyes ([P < 0.001, P = 0.006], P < 0.001, and P < 0.001, respectively). In the myopic patients, subfoveal CT, nasal CT, temporal CT, TCA, LA, SA values were statistically smaller in amblyopic eyes than in healthy eyes and control eyes ([P < 0.001, P = 0.002), [P = 0.004, P = 0.012], [P = 0.012, P = 0.032], [P < 0.001, P = 0.013], [P < 0.001, P = 0.024], and [P < 0.001, P = 0.047], respectively). The differences in the AL and choroidal parameters were due to myopia and hyperopia. Conclusion: The choroidal structural parameters of the amblyopic eyes were different from that of the healthy eyes.